Utilization of Furniture Waste into Handicrafts that Generate Sales Value in Beratwetan Village, Gedeg District, Mojokerto Regency - Achmad Muchammad; Hilmy Syahab; Afrida Sista Kurniasari; Alfi Lutfiah; Jayanti Devi Ikasari; Isna Qurrotul Aini (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2025)
Community empowerment is a development process in which local residents take the initiative to start social activities aimed at improving their conditions and overall quality of life. In this context, training programs are designed to enhance specific skills, knowledge, and attitudes to help individuals develop their potential based on the needs and resources of their local area. One relevant form of training to support regional development is handicraft training. This particular activity involved housewives from the POSPAUD community as the primary participants, while university students from the KKN program served as facilitators and organizers. The training adopted the Asset-Based Community Development (ABCD) approach, which emphasizes identifying and utilizing local assets and strengths to promote sustainable community growth and improved social structures. The results of this initiative showed that the training on making wooden cellphone stands was effective. Participants gained practical skills and knowledge, which sparked motivation among the POSPAUD members to explore entrepreneurship in the handicraft sector. Their motivation was influenced by their available free time as housewives and the existence of market opportunities for handmade products with selling value. Several key indicators are used to assess entrepreneurial motivation, including self-confidence, goal and task orientation, risk-taking ability, leadership, creativity, innovation, and a future-oriented mindset. Therefore, this training program served as a strategic intervention to empower the local community. It successfully encouraged the development of home-based businesses while fostering greater independence and economic resilience.